SOME CONSIDERATIONS ON THE ECONOMIC IMPORTANCE OF THE WHITE LICE OF THE CITRUS, Unaspis citri. - MOSQUERA-P., FELIPE (Revista Colombiana de Entomología, 1979)
Based on a study of the composition of colonies of the citrus snow scale Unaspis citri Comstock, the importance of this insect as an economic pest is argued. It was found that at a given moment, 86,5 - 95,5% of the specimens of a colony were non-active from a feeding point of view and in addition to this, 43,9 - 79,3% of the active forms represented by crawlers, are males that stop feeding, i. e. causing damage, after its second molt.